The impact of exchange rate movements on import demand behaviour of Ghana - Korankye-Boateng, George (2017)
A Thesis Submitted to the Department of Economics, Kwame Nkrumah University of Science and Technology, in partial fulfilment of the requirement for the degree of Master of Philosophy in Economics, 2016